REPRESENTATION OF THE VALUE OF FRIENDSHIP IN THE PERSPECTIVE OF ROLAND BARTHES IN THE ANIME JUJUTSU KAISEN SEASON 2 - Jesica Seftia Utari; Danang Trijayanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research aims to analyze the representation of friendship values in the Jujutsu Kaisen Season 2 anime using Roland Barthes' semiotic approach. The method used is qualitative descriptive with data collection techniques through observation in episodes 1–5 and literature studies. The analysis requires three different levels of meaning which include denotation, connotation and myth to study the scenes and dialogues and character interactions between Gojo Satoru and Suguru Geto. The results of the study show that friendship is dynamically represented through the values of najimu, amae, tatemae, and shuudan ishiki. The first level of friendship demonstration shows two characters who work together and maintain close ties as friends. The relationship shows emotional bonds between the two people who share trust and concern for each other. People see friendship through the mythical level as a bond that can endure between people who hold different values and face opposing beliefs. Anime functions as both an entertainment medium and a platform to show evolving social and cultural traditions that exist throughout Japanese society.